Development and Characterization of the Arterial Windkessel and Its Role During Left Ventricular Assist Device Assistance. Issue 8 (6th July 2015) - Capoccia, Massimo
Abstract Modeling of the cardiovascular system is challenging, but it has the potential to further advance our understanding of normal and pathological conditions. Morphology and function are closely related. The arterial system provides steady blood flow to each organ and damps out wave fluctuations as a consequence of intermittent ventricular ejection. These actions can be approached separately in terms of mathematical relationships between pressure and flow. Lumped parameter models are helpful for the study of the interactions between the heart and the arterial system. The arterial windkessel model still plays a significant role despite its limitations. This review aims to discuss the model and its modifications and derive the fundamental equations by applying electric circuits theory. In addition, its role during left ventricular assist device assistance is explored and discussed in relation to rotary blood pumps.